Effectiveness of structured teaching programme on knowledge regarding Prophylactic vaccination against cervical cancer among adolescent girls - Rintumol P.R; Dr. Hardeep Kaur; Dr. Amanpreet Kaur (International Journal of Vaccines, 2025)
Background: Adolescent health encompasses the variety of methods used to prevent, identify, or treat the health and wellness of young people. Adolescent health also includes the sexual and reproductive health of children and young adults. Women of all ages are susceptible to HPV infection. The human papillomavirus is the cause of cervical cancer . The HPV vaccine is an important main preventive measure against cervical cancer . Thus, it is important to acknowledge teenage girls' knowledge and comprehension of preventative cervical cancer vaccination. A structured teaching program (STP) was developed and put into place to improve the knowledge of preventive vaccination among teenage girls. Objectives: ·To assess the pretest level of knowledge regarding prophylactic vaccination against cervical cancer among adolescent girls in the control and experimental group. To develop and deliver a structured teaching programme regarding prophylactic vaccination against cervical cancer among adolescent girls. To assess the post-test level of knowledge regarding prophylactic vaccination against cervical cancer among adolescent girls in the control and experimental group. To assess the awareness of adolescent girls about preventative cervical cancer vaccinations before and after the test in both the experimental and control groups. To determine the relationship between teenage girls' awareness of preventative immunization against cervical cancer and chosen variables.Materials and techniques: For this study, a quasi-experimental research approach was used. Teenage girls from a few senior secondary schools in Jandiala Guru, District Amritsar, make up the study's population. This study included sixty pupils who satisfied the inclusion criteria. Using a straightforward nonrandomized sampling strategy, eligible subjects were chosen. To evaluate knowledge, a self-structured questionnaire was employed. Only the teenage girls in the experimental group received STP. A posttest was administered to both groups seven days later. Results: The results showed that following the implementation of the Structured Teaching Program, students in the experimental group experienced an overall increase in their knowledge. The mean pretest knowledge in the control group was 11.33±1.93 and the average posttest score was 13.46±2.708. The experimental group's mean knowledge score on the pretest was 13.46±2.708, and their mean score on the posttest was 18.4±3.88. At the p<0.05 level of significance, the difference between the pretest and posttest is statistically significant.In a nutshell statistical analysis of the data shows that the structured teaching program (STP) improved adolescents' understanding.
Keywords: adolescent girls. HPV Vaccination; cervical cancer; prophylactic vaccination; structured teaching program (STP)